Cesariana e risco de obesidade do nascimento até a adolescência : um estudo de coorte - Dal'Maso, Elizandra (2019)
Caesarean section has been studied as a possible risk factor for obesity. Several epidemiological studies have analyzed the relationship between cesarean section and obesity at specific stages of life, but the effect on the change in weight status over time is still poorly explored. Objective: To analyze the effect of cesarean section on obesity risk from birth to adolescence. Methods: Data from a cohort of children born between 1994 and 1999, who were part of the population-based study "Prevalence of passive smoking and its repercussions on the health of children under 5 years old", conducted in the city of Cuiabá-MT, Brazil, in 1999-2000 (1 st stage) and in 2009-2011 (2 nd phase) were used. In the first phase, 2,405 children aged between 0 and 5 years were randomly selected at basic health units when taken to comply with the schedule of vaccines for this age group. In this evaluation, general data on birth (phase 1) were obtained, such as birth weight and length and type of delivery, as well as family socioeconomic conditions and anthropometric measurements at the time of the research (phase 2). After approximately ten years, the participants were in adolescence (phase 3) and were located through the School Census. We interviewed 1,716 adolescents (71.4% of the base population), distributed in public and private schools in Cuiabá and in 18 other municipalities of the state, and 5 other capitals of Brazil. To test the difference between the proportions, the chi-square test was used, and to verify the association of cesarean section with obesity (BMI / age> +2 z-scores) throughout the three phases (birth, childhood and adolescence), generalized estimation equations (GEE) were performed, with binomial distribution and log-binomial models for repeated measures, controlled by confounding factors such as birth weight and length, gender, gestational age, breastfeeding, age and maternal education, economic status in childhood and maternal smoking during pregnancy. The time-exposure interaction term was evaluated to verify differences in the change in obesity risk over time between different types of delivery. The parents or guardians of the participants were informed about the purpose of the research and signed the Informed Consent Form (ICF) in both stages of the research. Results: Of the children evaluated in the first stage, 50.9% were male and 56.8% were born by cesarean section. Age, maternal education and family economic status were positively associated with cesarean section (p <0.01). There was a higher proportion of cesarean sections among children born over 3,000g and with a z-score ≥-2 for height at birth and childhood; among obese children, 61.9% were born from cesarean section. Childhood obesity was positively associated with cesarean section and the family's economic status. Birth weight was positively associated with obesity in both childhood and adolescence. Children born by cesarean section had higher obesity risk from birth to adolescence (RR = 1.22; 95% CI = 1.02-1.46), even after adjusting for covariates, when compared to those born by vaginal delivery. However, the time-exposure interaction term was not significant, indicating that there was no change in obesity risk over time. Conclusion: Caesarean section was positively associated with obesity at birth, childhood and adolescence, with constant obesity risk during the study period.